Midazolam infusions for therapeutic management of pediatric refractory status epilepticus: a systematic review - Johnson, K. Taneille; AlZadjali, Ammar; Al Nasseri, Dawoud; Cunningham, Jessie; Shoya, Kazuhiro; Hahn, Cecil D.; Basmaji, John; McKinnon, Nicole K. (Frontiers in Pediatrics, 2025)
ObjectiveWe aim to determine the optimal dosing of midazolam continuous intravenous infusions for the treatment of pediatric refractory status epilepticus (RSE).Data sourcesWe searched Medline ALL, Embase, Embase Classic, Cochrane CENTRAL, and Web of Science in March 2023 and again in February 2024.Study selectionRandomized and non-randomized studies involving pediatric patients who received continuous midazolam for the treatment of RSE were eligible. Two authors independently conducted screening, full-text review, and data extraction. All methods followed PRISMA reporting guidelines. A narrative data synthesis was performed due to data heterogeneity.Data extraction and synthesisNineteen studies (448 patients) proved eligible; 3 were randomized control trials, while 16 were non-randomized studies. All studies had concerns regarding the risk of bias. Overall, midazolam aborted seizures in 363/448 (81%) participants, with mean effective doses of 1.7–13.0 μg/kg/min (0.17–0.78 mg/kg/h). The remaining 85 participants (19%) who did not achieve seizure cessation received maximum doses of 1.7–32.0 μg/kg/min (0.17–1.92 mg/kg/h) prior to transitioning to another agent. Only 4 studies specified that boluses were given with each titration. Twelve studies reported that seizure cessation occurred at a mean time of 1.4–546.0 min (range 0–720 min) after midazolam initiation. In 8 of these studies, effective midazolam doses clustered at 2.0–5.0 μg/kg/min (0.12–0.30 mg/kg/h), with seizure cessation occurring within 10–70 min in 204/221 (92%) participants. Treatment-associated adverse events included intubation in 42/221 (19%) and hypotension requiring fluids or no intervention in 18/221 (8%). The studies did not differentiate between intubations performed as part of the study protocol or prior to midazolam infusion initiation nor did they specify whether hypotension was related to the co-administration of phenytoin or phenobarbital.ConclusionData supporting midazolam continuous infusion dosing are limited and heterogeneous. Our findings suggest a potential therapeutic window at rates of 2.0–5.0 μg/kg/min (0.12–0.30 mg/kg/h), with limited adverse risks. Earlier seizure cessation may be achieved by targeting this therapeutic window by starting treatment with higher doses than the typically used 1.0 μg/kg/min (0.06 mg/kg/h) or by rapidly escalating the dose. Systematic Review Registration: PROSPERO, identifier CRD42023413038.